(untitled) (One Health Journal of Nepal, 2023)
Introduction: One of the most effective and established therapies for the treatment of dehydration is oral rehydration therapy, which is convenient as it can be easily carried out in the home. Diarrhea in itself is not lethal, however, inadequate knowledge and poor practices among the primary caregiver; mothers lead to severe dehydration leading to death. The main objective of this study was to assess the mothers’ knowledge and practice regarding oral rehydration therapy for diarrhea among mothers of under-5 children. Methods: This cross sectional study was conducted with a sample size of 216. Relevant descriptive statistics were computed for all items. A semi-structured questionnaire was used for data collection while SPSS version 20 was used for analysis. Purposive sampling technique was used, by utilizing a semi-structured questionnaire. Results: The study highlighted that half of the mothers (52.4%) having under five aged children had fair knowledge about Oral Rehydration Solution (ORS) while one-fourth of the participants had poor (23.3%) and one-fourth of participants (24.3%) had good knowledge. More than half of the participants did not know the role of ORS in diarrhea. Half of the participants (58.2%) knew that either boiled or clean water was necessary for the preparation of ORS. Two–thirds (78.8%) of the participants knew that 1 liter of water is needed for 1 packet of ORS. Conclusions: Despite the rampant availability of information sources, the study shows the need for awareness and knowledge dissemination sessions to be conducted at the community level to upgrade the level of knowledge.